Bookish Carmelites in conflict: the sending of readings for religious of the Province of New Spain - García, Idalia; Romero, Xavier (Revista General de Información y Documentación, 2021)
The history of the conventual libraries that existed in the Viceroyalty of New Spain is a topic of study very neglected. Hence, there are so few works focused on recovering a part of the bibliographic past of the collections that all the religious orders formed from the XVI century until the first half of the XIX century. This reality contrasts with an important set of historical evidence that is preserved in Mexican repositories, and that show cultural practices close to those of the peninsula with certain nuances of different social realities. These collections were useful both for the daily work of evangelization and the strengthening of the values of the Catholic religion, and for the transmission of European values that had to adapt to the realities of crossbreeding. The remains of this bibliographical richness constitute inhabitants in public libraries and private, as much as objects little appreciated, except for few interested. Each book of this nature has elements of provenance that allow to relate it with any of these orders (Jesuits, Franciscans, Dominicans, Mercedarios, Augustinians, among others. However, few have been related to these books with some of the inventories or memories of preserved books. Even less have these books been linked to the lists of the crates that came through the transatlantic trade. This article aims shows the arrival of some drawers of books for the order of Carmen.
Keywords: Conventual Libraries; Religious Libraries; Order of the Carmen; New Spain; Book trade